Food Insecurity and Adaptation of Highland Communities in the North of Thailand - Sitthisuntikul, Katesuda (Journal of Community Development Research (Humanities and Social Sciences); Vol 10 No 1 (2560): January-March 2017, 2017)
There had been an ongoing concern about food security. This article used document analysis to investigate the factors of food security, the risks of food security and adaptation to such risks, from research reports relating to food security of highland communities in Mae Hong Son Province, Thailand. The result indicated the four factors explaining food security: natural resources, local wisdom, beliefs in supernatural beings, and socio-culture of sharing. In contrast, the risks of food security consisted of the growth of commercial agriculture causing contaminated food, natural resource degradation and climate change affecting food accessibility and uncertain production, and the change of community livelihoods relating to sustaining food from generation to generation. The adaptation of highland people to these risks included focusing on more organic agriculture to protect natural resource and obtain safety food, managing food sources to access food sufficiently, and reviving and transmitting local wisdom for food sustainability. However, it required the encouragement of external agencies.
Keywords: Adaptation, Food Security, Highland Communities, Natural Resource Depletion